2016
DOI: 10.4236/oalib.1102520
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Re-Emerging Tuberculosis: A Review

Abstract: Tuberculosis (TB) is a deadly disease that still remains a global burden despite of worldwide measures to curb the disease. As of 2015, the goals of the WHO STOP TB Strategy (2006-2015) have been met and the new WHO End TB Strategy (2015-2030) has been implemented with aim of eradicating the disease. Following that, further studies have demonstrated that TB is a disease that cannot be controlled purely by anti-tuberculous medication alone. It is widely understood that various factors such as rising income ineq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…These conditions are the cause of malnutrition that in many cases is severe and increases the risk of tuberculosis, even being a risk factor for the reemerging of the disease, especially in patients with BMI < 18.5, in our case the patient had a BMI of 12 in the moment of admission [10], [11]. Severe malnutrition, especially protein-energy malnutrition, causes immunity impairment especially cell-mediated immunity especially the delayed type hypersensitivity, that is the main defense mechanism of the host toward tuberculosis.…”
Section: Discussionmentioning
confidence: 52%
“…These conditions are the cause of malnutrition that in many cases is severe and increases the risk of tuberculosis, even being a risk factor for the reemerging of the disease, especially in patients with BMI < 18.5, in our case the patient had a BMI of 12 in the moment of admission [10], [11]. Severe malnutrition, especially protein-energy malnutrition, causes immunity impairment especially cell-mediated immunity especially the delayed type hypersensitivity, that is the main defense mechanism of the host toward tuberculosis.…”
Section: Discussionmentioning
confidence: 52%
“…Although this disease is curable, multi-drug resistance caused by improper treatment regimens or incompliance with regimens has made TB difficult to treat effectively. Also, TB was thought to be receding in the past decade, but there is evidence that it has been re-emerging in recent years (Shajahan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Malaysia had a total of 25,739 new cases, an annual TB incidence rate of 92 cases per 100,000 population, and an attributed mortality rate of 5.1 cases per 100,000 population [1]. Notably, the increasing trend of TB cases was observed in populous states, urban areas and industrialized cities [6] [14]. Previous studies in Malaysia have reported multiple factors associated with the risk in TB incidence [6] [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in Malaysia have reported multiple factors associated with the risk in TB incidence [6] [15]. One major contributory factor has been the influx of immigrants to Malaysia [6] [14]. Urban populations, especially those in crowded dwellings and slum areas, have been identified among the most susceptible population to TB infection [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation